Observation of Interior Facilities Standards Boutique Hotel in Bandung City - Izdianazia, Tasya; Firmansyah, Rangga; Farida, Ariesa; Cardiah, Tita (Pendhapa, 2023)
Boutique hotels are an attraction for tourists to do a staycation because this hotel has unique designs and characteristics with different themes. With that, boutique hotels in Bandung can be a solution for tourists to do staycations as an accommodation to refresh physically and mentally, which can increase hotel occupancy in Bandung. Based on the standard evaluation of boutique hotel interior facilities, these three boutique hotels already have the appropriate standardization according to the classification of star hotels based on the Decree of the Directorate General of Tourism No. 12/U/II/88. Boutique hotels still need provisions. So, Boutique Hotel will do research by observing and using descriptive qualitative research methods on several 3-star boutique hotels in the city of Bandung by making comparisons of the three hotels regarding standards at boutique hotels based on the shape of the facade, the style of the building, the theme, and the interior atmosphere. And hotel staff services. In addition, based on the organization of space in boutique hotels. So, this study found that boutique hotels have used boutique hotel standards and still use the standards of existing 3-star hotels. Thus, the standards in the three hotels can act as a reference in designing boutique hotels